2019
DOI: 10.1089/ars.2018.7507
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin5 Controls Vertebrate Ciliogenesis by Modulating Mitochondrial Reactive Oxygen Species

Abstract: Prdx5 plays protective roles in mitochondria and is critical for normal cilia development by regulating the levels of ROS. The loss of Prdx5 is associated with excessive production of ROS, resulting in mitochondrial dysfunction and aberrant ciliogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Many studies have shown that Prx5 has antioxidant protective functions and can effectively remove oxidative stress [ 17 ] [ 23 ]. Thus, we investigated whether Prx5 is involved in the occurrence of cardiac hypertrophy and dysfunction by regulating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that Prx5 has antioxidant protective functions and can effectively remove oxidative stress [ 17 ] [ 23 ]. Thus, we investigated whether Prx5 is involved in the occurrence of cardiac hypertrophy and dysfunction by regulating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, overexpression of Prx3 prevents cardiac hypertrophy and failure after myocardial infarction in mice [ 15 ]. As an important member of the Prx family, Prx5 has antioxidant protective functions and can effectively remove reactive oxygen species (ROS) [ 16 , 17 ]. However, the involvement of Prx5 in cardiac hypertrophy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal phenotypes, such as reduced glucose utilization and increased fatty acid consumption, lead to the accumulation of toxic intermediates in diabetic patients [70] . For example, excessive ROS can damage DNA, lipids, endoplasmic reticulum, peroxisomes, mitochondria and other cellular components and organelles [71] . Mitochondria not only participate in the synthesis of ATP, but also metabolize fatty acid, lactic acid and ketone body.…”
Section: Discussionmentioning
confidence: 99%
“…The critical balance of ROS is indispensable for embryonic development, and the members of thiol peroxidases have been studied for their essential roles in early vertebrate embryogenesis, for example, Prdx1 plays a crucial role in pronephros development during embryogenesis [24], and Prdx5 has been found to control vertebrate ciliogenesis [25]. In addition to Prdxs, GPx3 is involved in posterior development during vertebrate embryonic development [26].…”
Section: Introductionmentioning
confidence: 99%